Early diagnosis of Parkinson’s disease: biomarker study - Li, Jing; Zhang, Mei; Yu, Chuan-Qing; Xue, Min; Hu, Pan-Pan (Frontiers in Aging Neuroscience, 2025)
Parkinson’s disease (PD) is a common chronic degenerative disease with age-dependent increasing prevalence in the elderly. Non-motor symptoms include sensory deficiencies, autonomic dysfunction, psychological and cognitive abnormalities; while motor symptoms are bradykinesia, myotonia, resting tremor, and postural balance difficulties. The clinical diagnosis of PD depends mainly on patients’ medical history and physical examination. It is highly important to realize early detection of PD, and biomarkers are a valuable tool in this regard. The present study reviewed the findings of researches from the last few years, involving the advancements in the study of PD biomarkers in blood, cerebrospinal fluid, saliva, urine, tears, imaging, and pathology.